MAQASID AL-SHARI'AH REVISITED: REASSESSING LEGAL RATIONALITY IN ISLAMIC ECONOMIC TRANSACTIONS - Ahmed Al Fahad; Fatimah Al Rashid; Emma Brown (Sharia Oikonomia Law Journal, 2026)
Maq??id al-Shar??ah has re-emerged as a central framework for evaluating the ethical and legal dimensions of Islamic economic transactions amid increasing complexity in global financial systems. Contemporary practices often emphasize procedural compliance, creating a gap between formal legality and substantive justice. This study aims to reassess legal rationality by examining how maq??id can function as a foundational framework for guiding economic transactions beyond rule-based validation. A qualitative normative–juridical research design is employed through systematic analysis of 88 legal and regulatory documents, including classical jurisprudential texts, fatwas, and institutional guidelines across multiple jurisdictions. Analytical matrices and thematic coding are used to identify patterns of maq??id application, institutional integration, and interpretive variation. The findings reveal that maq??id is unevenly operationalized, with stronger integration in policy-oriented frameworks and centralized governance systems, while doctrinal and case-based applications remain selective and inconsistent. Institutional embedding of maq??id enhances coherence and ethical alignment, whereas fragmented application reinforces formalistic tendencies. The study concludes that reconfiguring legal rationality requires transforming maq??id from a conceptual ideal into an operational governance tool capable of aligning legal form with ethical substance in contemporary Islamic finance.